Kyrgyz Republic - Public Expenditure Review : Fiscal Policies for Growth and Poverty Reduction, Volume 1. Main Report - World Bank (Washington, DC, 2013)
The Kyrgyz Republic suffered severe shocks during the early years of independence, loosing its traditional markets in the Former Soviet Union republics, as well as substantial transfers and subsidies from the Soviet Union, that included a falling GDP during the first five years of transition. These circumstances prompted the Kyrgyz Republic to adopt a wide range of reforms to accelerate the transition to a market economy, emphasizing price and trade liberalization, and the shift of ownership of state assets to the private sector, including land, and most state-owned enterprises (SOEs). Since the mid-l990s, the economy has shown steady signs of recovery. Despite these favorable developments, the Kyrgyz Republic remains the second poorest of the FSU republics, and one of the poorest countries in the world. Absolute poverty affected about half of the population in spite of progress made in 2001, and, although poverty is highest in rural areas, there are large regional disparities, where transient poverty is high as a result of high consumption volatility. Access to public services such as water and sewerage, electricity, district heating, and telecommunication services, is very low. This Public Expenditure Review (PER) has sought to provide a strategic framework for fiscal adjustment and public expenditure reform, consistent with the government's objectives for accelerated growth and poverty reduction. The broad contours o f the strategy are: To stabilize the government's finances through stronger revenue, and expenditure management instruments and institutions, as well as through debt relief; to re-align sector policies with the most essential country priorities, with a general thrust toward improving targeted, and efficient use of resources in both social and public infrastructure sectors; to revamp the public administration to improve policy implementation and service delivery; and, to secure external financial support. Given the fragile external debt situation and the extent of poverty, priority has to be given to fiscal adjustment and the expenditure reform agenda. Government performance needs to be monitored, particularly at the grass roots levels, through systematic diagnoses of institutional problems, and through quantitative performance indicators, to monitor progress and competition in public service delivery.